Determination of the shelf life of the API morpholinium 2-((4-(2-methoxyphenyl)-5-(4-pyridyl)-4H-1,2,4-triazol-3-yl)thio)acetate - A. H. Kaplaushenko; S. O. Vasyuk; A. I. Avramenko; M. Zh. Koichev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
This study determined the shelf life of the active pharmaceutical ingredient (API) morpholinium 2-(4-(2-methoxyphenyl)-5-(4-pyridyl)-4H-1,2,4-triazol-3-yl)thio)acetate by determining its quantitative storage characteristics.